Sistem Pendukung Keputusan Penentuan Calon Penerima Beasiswa Prestasi di Universitas Amikom Yogyakarta - Mariko, Muhammad; Yaqin, Ainul (STMIK Budi Darma, 2019)
Amikom Yogyakarta University provides various types of scholarships to students, one of which is an achievement scholarship. the selection process requires precision and also fast, so that the results obtained are in accordance with the provisions, if the selection process is done manually then it will take a long time and easy errors occur. Decision support systems using the Tsukamoto fuzzy method can help select scholarship recipients by performing mathematical calculations by the system and produce weighting criteria for each student as a reference in decision makers. Based on the results of the research of each criteria weight, namely GPA, achievement and assessment of parents obtained test results with an accuracy of 80%.